(untitled) (Journal of Management and Social Sciences, 2022)
The rigid compartmentalization of the executive, legislative and judicial arms of government that is practiced at the sub-national level in Nigeria’s fourth republic is a function of the retention of the presidential system of government at the inauguration of Nigeria’s Fourth Republic in 1999 The critical component of the system is the operation and respect for checks and balances. The principal problem that afflicts executive-legislature relations at the sub-national level in Nigeria was the issue of imbalance in power. Executive domination that is rooted in historical and structural reasons reduces the State Houses of Assembly to junior partners in their activities. Notwithstanding the modus of their operations, the paper argues that cordial relations rather than conflict is critical in meeting/addressing the hopes and aspirations of the citizens whose primary concern is the growth and development of the society. The paper adopts a qualitative approach through interview sessions with key informants who were participants in the events of Kwara and Osun states in Nigeria that are cases of focus. In addition to empirical data, literatures, including journals, newspapers, books are consulted for the study The paper finds that the gains that were recorded in the two states due to the smooth relationship were remarkable, it, however, concluded that if further checks and balances are deepened in their relations, the level of success would be enhanced and the developmental strides be would accelerated. Keywords Executive, legislature, presidential, sub-national, checks and balances, imbalance